Variation in human sweet taste receptor may result in different levels of sweet intensity variability between sweet stimuli - Waksmonski, James C. (Kansas State University, 2016)
Understanding the physiological activation and genetic variation of the sweet taste receptor (T1R) can improve formula optimization for products intended for a population of genetically diverse people. Computer modeling and cell culture techniques have thoroughly described the structure and binding sites of the T1R. The structure contains two subunits (T1R2 and T1R3) with multiple domains where sweet molecules can interact. The interaction takes place between individual molecules and amino acid residues of the T1R. The residues with which individual molecules interact differs between sweeteners. Person-to-person differences in the residue sequence of the T1R can arise from variation in the genes that encode the T1R (TAS1R), potentially effecting the function of the receptor. As a result of the specificity of binding interactions, genetic variation may affect sensitivity to some sweeteners, while sensitivity to other sweeteners remains normal. Therefore, it can be hypothesized that the level of person-to-person sweetness sensitivity variation may differ for each sweetener depending on the binding site of the molecule and site of T1R variation. The T1R structure, binding sites, and genetic variation will be reviewed, as well as potential parameters to predict the degree of sensitivity variation and formulation strategies to minimize the effects of sensitivity variation.
Keywords: Sensory; Sweet; Receptor; T1R; Genetic Variation; Sweet Intensity